Ionization-induced tautomerization in cytosine and effect of solvation - Das, Tamal; Ghosh, Debashree (Journal of Physical Chemistry A, 2014)
The recent observation of excitation-induced tautomerization in gas-phase cytosine motivated us to investigate the possibility of facile tautomerization in ionized cytosine and the effect of solvation on the tautomerization barriers. The tautomerization mechanisms were characterized at the density functional theory (DFT)omega B97X-D and coupled-cluster singles and doubles (CCSD) levels of theory. Vertical and adiabatic ionization energies (VIEs and AIEs, respectively) of the tautomers of cytosine and the microsolvated species were calculated with the equation-of-motion ionization-potential coupled-cluster (EOM-IP-CCSD) method. We observed that, in microsolvated cytosine, the solvatochromic shifts of the VIEs can be both blue- and red-shifted depending on the tautomers. This is explained by the analysis of the charge dipole interactions between the cytosine and water molecules. We noticed that, upon ionization, gas-phase tautomerization barriers are reduced by 0-4 kcal/mol, whereas microsolvated (with one water) tautomerization barriers are reduced by 4-5 kcal/mol. We also investigated the tautomerization process in solvation using a continuum model with one active water molecule in the quantum mechanical region. We noticed that, even though bulk solvation has a significant effect on ionization energies, its effect on the ionization-induced tautomerization barrier is minimal.